Postmigrantische Visionen Erfahrungen - Ideen - Reflexionen - Hill, Marc; Yildiz, Erol (Postmigrantische Studien, 2018)
In order to re-consider the relationship between migration and society, Marc Hill and Erol Yildiz turn established certainties over and include the experience of migration. Their focus is on shared stories that show the versatility of urban community life. By doing so, they make migration the starting point of other analyses of society. Postmigrant visions serve as categories of the analysis of social situations of mobility and diversity, make ambiguities and marginalized memories that articulate social conditions visible. Contrasting ideas are put in the focus without overlooking conditions of dominance and structural barriers.